Comparison between Satellite Water Vapour Observations and Atmospheric Models’ Predictions of the Upper Tropospheric Thermal Radiation - J. R. Dim; T. Y. Nakajima; T. Takamura; N. Kikuchi (Advances in Meteorology)
Atmospheric profiles (temperature, pressure, and humidity) are commonly used parameters for aerosols and cloud properties retrievals. In preparation of the launch of the Global Change Observation Mission-Climate/Second-Generation GLobal Imager (GCOM-C/SGLI) satellite, an evaluation study on the sensitivity of atmospheric models to variations of atmospheric conditions is conducted. In this evaluation, clear sky and above low clouds water vapour radiances of the upper troposphere obtained from satellite observations and those simulated by atmospheric models are compared. The models studied are the Nonhydrostatic ICosahedral Atmospheric Model (NICAM) and the National Center for Environmental Protection/Department Of Energy (NCEP/DOE). The satellite observations are from the Terra/Moderate Resolution Imaging Spectroradiometer (Terra/MODIS) satellite. The simulations performed are obtained through a forward radiative transfer calculation procedure. The resulting radiances are transformed into the upper tropospheric brightness temperature (UTBT) and relative humidity (UTRH). The discrepancies between the simulated data and the observations are analyzed. These analyses show that both the NICAM and the NCEP/DOE simulated UTBT and UTRH have comparable distribution patterns. However the simulations’ differences with the observations are generally lower with the NCEP/DOE than with the NICAM. The NCEP/DOE model outputs very often overestimate the UTBT and therefore present a drier upper troposphere. The impact of the lower troposphere instability (dry convection) on the upper tropospheric moisture and the consequences on the models’ results are evaluated through a thunderstorm and moisture predictor (the K-stability index). The results obtained show a positive relation between the instability and the root mean square error (RMSE: observation versus models). The study of the impact of convective clouds shows that the area covered by these clouds increases with the humidity of the upper troposphere in clear sky and above low clouds, and at the same time, the error between the observations and the models also increases. The impact of the above low clouds heat distribution on the models is studied through the relation between the low clouds cover and their effective emissivity. The models’ error appears to be high at midrange effective emissivity clouds.